2014
DOI: 10.1063/1.4887751
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical activity to control obesity problem in Malaysia

Abstract: Obesity is defined as a condition in which an individual has an excess of body fat and it is accumulated to the extent that it can lead to numerous health problems and decreases the quality and length of life. Overall, the contributing factor to obesity varies. Lack of physical activity and increased sedentary behaviour has been identified as the causes of weight gain and various health implications including obesity. Rapid development in industrialization and urbanization has brought Malaysia to be the next m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A number of studies used SDM to simulate the effect of PA behaviours or policy interventions on obesity outcomes (n = 7) [65][66][67][68][69][70][71]. Several (n = 3) used the Prevention Impacts Simulation Model (PRISM) (an SDM) to project the reduction in deaths and costs from PA promotion and other obesity prevention efforts [72][73][74].…”
Section: Prediction (Simulation)mentioning
confidence: 99%
“…A number of studies used SDM to simulate the effect of PA behaviours or policy interventions on obesity outcomes (n = 7) [65][66][67][68][69][70][71]. Several (n = 3) used the Prevention Impacts Simulation Model (PRISM) (an SDM) to project the reduction in deaths and costs from PA promotion and other obesity prevention efforts [72][73][74].…”
Section: Prediction (Simulation)mentioning
confidence: 99%
“…Shaw et al (2006) supported the use of exercise as a weight loss intervention, particularly when combined with dietary change (Shaw, Gennat, O'Rourke, & Del Mar, 2006). A recent systematic review and meta-analysis to evaluate the efficacy of aerobic exercise programmes in overweight and obese populations reported that moderate-intensity aerobic exercise programmes of six to twelve months induce a modest reduction in weight and waist circumference in overweight and obese populations (Abidin, Zaibidi, & Zulkepli, 2014).…”
Section: Obesitymentioning
confidence: 99%